Politics and conflict in Bolivia - Silva, Eduardo (2012)
The mass mobilizations of the early 2000s that helped bring Evo Morales and his party to power raised expectations for the (re)incorporation of popular sectors, peasants, and indigenous peoples in the political arena. This article analyzes why in his second government (2010-2014) this expectation gave way to deepening conflict with movements that had helped him win the presidency. It argues that the inevitable setting of policy priorities generated strong tensions in the government’s heterogeneous social coalition forged during anti-neoliberal mobilization.